"I Don't Mix Much": Language Mixing in Transnational Polish-British Culture 2012–18. Issue 1 (19th May 2020) - Finer, Emily
Language mixing by migrants in the process of acquiring a new language is often treated as a symptom of their linguistic deficit, a stage to be overcome on the way to full bilingualism. Yet language mixing is also a creative process, a way to build community, maintain the transnational family, and restore cultural capital lost in migration. The cultural representations of the lives of post-EU accession Polish migrants in the UK discussed in this article – in an advertisement for an online shopping website, a novel for teenagers in English and Polish translation, and a series of illustrations with captions – use different strategies to tell stories of language acquisition and loss. I argue that ten years after Joanna Rostek and Dirk Uffelmann asked "Can the Polish Migrant Speak?" it is time to ask how the Polish Migrant speaks, and to offer an answer with more nuance than "in Polish" or "in English" by taking code-switching and translanguaging into account. Tweet: How are the languages spoken by Polish migrants in the UK represented in culture?#CzegoSzukasz, @SarahCrossan, andMonika Szydłowska's @Na_emigracji?